PENGARUH SEDUHAN RIMPANG KUNYIT KUNING (Curcuma longa Linn.) TERHADAP PEMAHAMAN BACAAN - Nathaniel Nickander Pramuditha Pekasa; Fen Tih; Julia Windy Gunadi (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2021)
Increasing globalization makes humans need the knowledge to compete globally. One way to increase knowledge is by reading. Reading comprehension is the process of interpreting a reading in order to gain a thorough knowledge of the passage. Therefore it is necessary to consume beverages to improve energy and cognitive function. In this study, the researcher used yellow turmeric rhizome steeping as an enhancer of cognitive function. The objective of this research was to determine the effect of consuming yellow turmeric rhizome steeping on the cognitive function which is reading comprehension. This study was quasi-experimental, comparative using pretest and post-test design, conducted on 30 men aged between 18-22 years. Participants were asked to do a reading comprehension test (pretest) than consume 200 cc of water mixed with 10 grams of yellow turmeric rhizome powder. Participants took rest for 90 minutes and asked to do a reading comprehension test (post-test). The measured data was the reading comprehension test score, in the form of a correct answer of 10 questions. Data were analyzed using Wilcoxon Signed Rank Test. The average score of correct answers increased very significantly, before consuming yellow turmeric steeping was 47,33 to 73,33 after consuming yellow turmeric rhizome steeping with p < 0,001. Therefore yellow turmeric rhizome steeping increases reading comprehension.